1956
DOI: 10.1002/jsfa.2740070307
|View full text |Cite
|
Sign up to set email alerts
|

Chemical investigation of the leaves of Anona senegalensis. I.—Constituents of the leaf wax

Abstract: The constituents of the leaf wax of Anona senegalensis have been investigated when hard and soft waxes were isolated. Both yielded higher saturated fatty acids. In addition, primary alcohols (C28, C30, C32) and palmitone were obtained from the hard wax, and unsaturated acids, palmitone, and yellow sesquiterpene oils from the soft wax. The soft wax was effective against Sclerostome larvae from horse faeces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1958
1958
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…More recently, our own studies on the plant (Adzu et al, 2003a) revealed that the methanol extract of the root bark of this plant has analgesic and anti-inflammatory activities that might be exerted through peripheral mechanisms and phytochemical tests indicating the presence of saponins, tannins and resins. The plant has been reported to contain in addition, wax, alkaloids (Philipov et al, 1995;You et al, 1995), proteins, amino acids, antraquinones (Bamba et al, 1984;Burkill, 1985;Ekpendu et al, 1998), sterols, glycosides, flavonal terpenoids (Mackie and Misra, 1956;Mackie and Ghatce, 1958;Adesogan and Durodola, 1976;Fatope et al, 1996;Sahpaz et al, 1996) and terpenes (Ekundayo and Oguntimein, 1986).…”
Section: Introductionmentioning
confidence: 96%
“…More recently, our own studies on the plant (Adzu et al, 2003a) revealed that the methanol extract of the root bark of this plant has analgesic and anti-inflammatory activities that might be exerted through peripheral mechanisms and phytochemical tests indicating the presence of saponins, tannins and resins. The plant has been reported to contain in addition, wax, alkaloids (Philipov et al, 1995;You et al, 1995), proteins, amino acids, antraquinones (Bamba et al, 1984;Burkill, 1985;Ekpendu et al, 1998), sterols, glycosides, flavonal terpenoids (Mackie and Misra, 1956;Mackie and Ghatce, 1958;Adesogan and Durodola, 1976;Fatope et al, 1996;Sahpaz et al, 1996) and terpenes (Ekundayo and Oguntimein, 1986).…”
Section: Introductionmentioning
confidence: 96%
“…Previous chemical studies of the stem and root barks of A. senegalensis have reported the isolation of diterpenoids (4,5), some of which showed antitumor and antibacterial activities (5). The leaves have also been analysed for alcohols, fatty acids, carbohydrates, glycosides, proteins, amino acids and sterols (6). An unidentified sesquiterpenoid in the leaves was considered to possess larvicidal properties (7).…”
Section: Introductionmentioning
confidence: 99%
“…From the root bark, Okoye and coworkers [44] identified diterpenoid, kaur-16-en-19-oic acid or kaurenoic acid as phytochemical constituents responsible for the antibacterial effects. A. senegalensis possess wax, alkaloids [45] proteins, amino acids, antraquinones [46], sterols, glycosides, flavonols, terpenoids [47] and terpenes [48].…”
Section: A Senegalensis Lmentioning
confidence: 99%